Feasibility and Safety of a Simple Non-cystoscopic Double-J Tube Removal Technique in Children - Bao, Qiao; Lao, Weihua; Shi, Tong; Ouyang, Keyu; Ma, Sai; Zhang, Wen; Lin, Yankun (Frontiers in Pediatrics, 2021)
Objective: Double-J tube placement is an important procedure during upper urinary tract surgery. A primary drawback is the requirement of a second double-J tube removal under a cystoscope. Therefore, a simple and feasible alternative is required to remove the double-J tube without cystoscopy. The present study reported the feasibility and safety of a simple non-cystoscopic double-J tube removal technique. Method: We retrospectively analysed children who underwent pyeloplasty and ureterovesical reimplantation between June 2015 and August 2021. A simple device (a catheter with a suture) was used to pull out the double-J tube. Patient characteristics, detailed surgical procedures, success and complication rates and reasons for failure were evaluated. Result: A total of 613 children were included. The mean age of patients was 6.2 months (3 months−14 years). Non-endoscopic methods were used to remove the double-J tube in all except 6 patients (0.9%). Of the 6 patients who required ureteroscopy or cystoscopy, 4 had retraction of the double-J tube into the ureter, and 2 (0.6%) had bladder stones. Of the 613 patients, 479 (76.0%) required one attempt, 127 (20.1%) required two attempts and 19 (3.0%) required several attempts. No serious postoperative complications occurred in all patients. The most common complications were gross haematuria (22.5%), pain urinating (17.9%), difficulty in urinating (3.6%), foreskin injury (1.7%) and penile oedema (1.3%). No urethral strictures developed during the follow-up period. Conclusion: The study results demonstrated that the modified and simple non-cystoscopic double-J tube removal technique is a safe and an effective alternative to cystoscopy in clinical practice.